2022
DOI: 10.7759/cureus.26141
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin-Induced Acute Psychosis in Patients Infected With COVID-19 Pneumonia

Abstract: Coronavirus disease 2019 (COVID-19) pneumonia is an infection of the lungs that causes severe inflammation in the lungs' alveoli. It causes alveoli to fill with fluid, blood clots, and sometimes even pus. Patients who are infected with COVID-19 pneumonia experience severe cough, shortness of breath, fever, fatigue, chest pain, night sweats, chills, loss of appetite, etc. During the initial phase of the COVID-19 pneumonia pandemic, it was thought that ivermectin might be helpful in patients infected with COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During the disease period, hydroxychloroquine, oseltamivir, and azithromycin were included in the recommendations of the World Health Organization, and we applied these treatments to our patients. However, among the treatment modalities, these drugs are no longer among the treatment recommendations because of their side effects or because of their ineffectiveness [ 30 ]. Especially, patients in the ICU benefited from antibiotics, which showed that bacterial superinfections play an important role in the progress of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…During the disease period, hydroxychloroquine, oseltamivir, and azithromycin were included in the recommendations of the World Health Organization, and we applied these treatments to our patients. However, among the treatment modalities, these drugs are no longer among the treatment recommendations because of their side effects or because of their ineffectiveness [ 30 ]. Especially, patients in the ICU benefited from antibiotics, which showed that bacterial superinfections play an important role in the progress of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Antiretrovirals such as remdesivir have emergency use authorization (EUA) for infants > 28 days and > 3.5 kg [ 20 ], while Paxlovid and monoclonal antibodies have EUA for children 12 years and older [ 21 ]. A double-blind study comparing ivermectin vs. placebo showed decreased viral load in COVID-19 adult patients, but the use of the same has not been evaluated adequately with the associated side effects [ 22 - 23 ]. The Centers for Disease Control and Prevention (CDC) has declared vaccination for COVID-19 safe for pregnant women, and it is prudent to vaccinate expecting mothers in the last trimester so the fetus can have the passive transfer of protective antibodies, given the information that vaccine-based immune response is maximum for three months duration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the initial phase of the COVID-19 pneumonia pandemic, it was thought that ivermectin might be helpful in patients infected with COVID-19 pneumonia, but this was later proven to be false due to its severe risks/side effects. The Infectious Disease Society of America (IDSA) recommends against the use of ivermectin for COVID-19 pneumonia [ 34 ]. Future studies should focus on the quality and RCT study design in patients with varying degrees of severity.…”
mentioning
confidence: 99%